Claudin‐5 regulates blood‐brain barrier permeability by modifying brain microvascular endothelial cell proliferation, migration, and adhesion to prevent lung cancer metastasis. (29th September 2017) - Ma, Shun‐Chang; Li, Qi; Peng, Jia‐Yi; Zhouwen, Jian‐Long; Diao, Jin‐Fu; Niu, Jian‐Xing; Wang, Xi; Guan, Xiu‐Dong; Jia, Wang; Jiang, Wen‐Guo
Summary: Aims: To investigate the roles of Claudin‐5 (CLDN5) in regulating the permeability of the blood‐brain barrier (BBB) during lung cancer brain metastasis. Results: By silencing and overexpressing the CLDN5 gene in human brain vascular endothelial (hCMEC/D3) cells, we demonstrated the attenuation of cell migration ability and CLDN5's significant positive role in cell proliferation in CLDN5‐overexpressing hCMEC/D3 cells and observed the opposite result in the CLDN5 knockdown group. The reinforced CLDN5 expression reduced the paracellular permeability of hCMEC/D3 cells and decreased the invasion of lung adenocarcinoma A549 cells. Overall, 1685 genes were found to be differentially expressed between the CLDN5‐overexpressing cells and the control cells using the Affymetrix Human Transcriptome Array 2.0 (HTA 2.0), and the function of these genes was determined by Gene Ontology and pathway analyses. The possible biological functions of the 1685 genes include cell proliferation, adhesion molecules, and the Jak‐STAT, PI3K‐Akt, Wnt, and Notch signaling pathways. The identified sets of mRNAs that were specific to CLDN5‐overexpressing hCMEC/D3 cells were verified by a qRT‐PCR experiment. Conclusion: CLDN5 regulates the permeability of BBB by regulating the proliferation, migration, and permeability of hCMEC/D3 cells, especially through the cell adhesion molecule signaling pathway, to enhance the function of the tight junctions, which was involved in reducing the formation of lung cancer brain metastasis.